Study on Mechanical Properties and Damage Evolution of High-Porosity Concrete under Cyclic Loading and Unloading - Dong Zhang (Hindawi Limited, 2021)
Understanding the mechanical properties and energy response of high-porosity concrete under the cyclic loading and unloading is the foundation of road construction in sponge city. In this study, the concrete with the porosity of 15% was taken as the research object, and the cyclic loading and unloading tests on the high-porosity concrete were performed under the stress amplitude of 25 MPa, 30 MPa, and 35 MPa in the elastic stage. The effects of stress amplitude and cycle number on the mechanical characteristics and damage evolution law of concrete were obtained. The experimental results show the following. (1) With the increase of cycle number, the loading and unloading elastic modulus of concrete under different stress amplitudes first increases and then decreases; the greater the stress amplitude, the faster the growth and deceleration of the loading and unloading elastic modulus. (2) With the increase of the cycle number, the peak strain and residual plastic deformation increase. (3) The greater the stress amplitude, the higher the damage of concrete; with the increasing number of cyclic loading and unloading, the damage of concrete is enhanced gradually. When the damage variable value is 1, the relationship between the cycle number and the initial stress amplitude satisfies a negative exponential function.